Seleção precoce para diâmetro em um teste de progênies de Myracrodruon urundeuva atacado por patógeno - Santos, Tainara da Silva (Universidade Federal de São Carlos, 2021)
Myracrodruon urundeuva (Anacardiaceae), known as “aroeira”, occurs naturally from Ceará to the Argentine Chaco and is classified as an endangered species in Brazilian and global levels. A M. urundeuva progeny test was recently diagnosed with severe damage to the trunk, showing symptoms of stem rot and high mortality due to a pathogen attack. The present work had as objectives (i) to carry out the identification of the pathogen, (ii) to quantify the level of infestation in the plantation over the years, raising a history of the area using vegetation indexes (NDVI) estimated from satellite maps and mortality data measured in the field, (iii) to determine if there is an association between the occurrence of the disease and the infestation of termites and borers observed in the planting, (iv) estimate the correlation between three ages regarding the stability of the test amidst disturbance with the increasing mortality caused by the pathogen and (v) determine the effectiveness of NDVI analysis in detecting mortality in plantations. Measurements of tree diameter and survival were made at the ages of 11, 16 and 22 years. The pathogen has been identified as Aspergillus niger causing red rot in sisal (Agave sisalana Perrine ex. Engelm). For tree diameter, the likelihood ratio test revealed that there are no significant differences among progenies at the three ages, but the heritability coefficient among progenies means for diameter ranged from median (0.32) to relatively high (0.44), indicating the possibility of genetic gain. The repeatability coefficient was medium (0.34 ± 0.03) for diameter, with a strong correlation among years, which indicates the potential for gains with an early selection. The percentages of survival at ages 11, 16 and 22 years were 95.7%, 92.1% and 86.1%, respectively. We found spatial dependence of survival among progenies, hindering the selection of resistant genotypes. The percentage of mortality obtained from NDVI was highly correlated with the mortality measured in the field, being, therefore, it is a valid and efficient method for the proposed use, besides being of low cost and easy to carry out.
Early selection for diameter in a Myracrodruon urundeuva progeny test under patogen attack
Keywords: NDVI; Aspergillus niger; Coeficiente de repetibilidade; Herdabilidade; CIENCIAS BIOLOGICAS::GENETICA